Short-snouted toothless ichthyosaur from China suggests Late Triassic diversification of suction feeding ichthyosaurs. - P Martin Sander (Public Library of Science (PLoS), 2011)
Background Ichthyosaurs were an important group of Mesozoic marine reptiles and existed from the Early Triassic to the early Late Cretaceous. Despite a great diversity in body shapes and feeding adaptations, all share greatly enlarged eyes, an elongated rostrum with numerous conical teeth, and a streamlined body. Methodology/principal findings Based on new material from China and the restudy of Shastasaurus pacificus, we here reinterpret the classical large-bodied Late Triassic ichthyosaur genus Shastasaurus to differ greatly from the standard ichthyosaurian body plan, indicating much greater morphological diversity and range of feeding adaptations in ichthyosaurs than previously recognized. Phylogenetic analysis indicates a monophyletic clade consisting of the giant Shonisaurus sikanniensis, Guanlingsaurus liangae, and Shastasaurus pacificus to which the genus name Shastasaurus is applied. Shastasaurus liangae comb. nov. is from the Late Triassic (Carnian) Xiaowa Formation of Guizhou Province, southwestern China. The species combines a diminutive head with an entirely toothless and greatly reduced snout. The species also has by far the highest vertebral count among ichthyosaurs (86 presacral vertebrae and >110 caudal vertebrae), a count that is also very high for tetrapods in general. A reduced toothless snout and a diminutive head is also apparently present in the giant S. sikanniensis and presumably in S. pacificus. Conclusions/significance In analogy to many modern odontocetes, Shastasaurus is interpreted as a specialized suction feeder on unshelled cephalopods and fish, suggesting a unique but widespread Late Triassic diversification of toothless, suction-feeding ichthyosaurs. Suction feeding has not been hypothesized for any of the other diverse marine reptiles of the Mesozoic before, but in Shastasaurus may be linked to the Late Triassic minimum in atmospheric oxygen.